Is Islamic insurance an alternative to conventional insurance? - Htay, Sheila Nu Nu; Syed, Ahmed Salman (2013)
The significance and importance of Takaful in the Islamic Finance has captured the attention Muslim communities in today’s world. Takaful can be seen as an alternative to conventional insurance due to its strong foundation of Islamic principles which are based on the concept of brotherhood, mutual co-operation and solidarity. It has become a fast growing and developing industry with great potential and has certainly evolved into a comprehensive system which eliminates non-Shari’ah compliant features such as interest, uncertainty and gambling that exist in the conventional insurance.